Halogen and Hydrogen Bonding Benzothiophene Diol Derivatives: A Study Using ab initio Calculations and X‐Ray Crystal Structure Measurements. Issue 2 (12th November 2014) - Cadoni, Enzo; Ferino, Giulio; Pitzanti, Patrizia; Secci, Francesco; Fattuoni, Claudia; Nicolò, Francesco; Bruno, Giuseppe
Abstract The aim of this study is to describe and compare the supramolecular interactions, in the solid state, of chloro‐, bromo‐, and iodobenzothiophene diols. The compounds were obtained through organo‐catalyzed reactions starting from 3‐substituted halobenzothiophene carbaldehydes. Energies of the noncovalent interactions were obtained by density functional theory calculations. Bond distances and angles were found to be in accordance with those determined by X‐ray structure analysis. anti‐Bromobenzothiophene derivatives showed strong halogen⋅⋅⋅π interactions between bromine and the heterocyclic phenyl ring, corresponding to an energy of 7.5 kcal mol−1. syn‐Bromo and syn‐iodo derivatives appeared to be isostructural, showing X⋅⋅⋅O (carbonyl) interactions, π stacking, and formation of extended hydrogen bonding networks. In contrast, the chloro derivatives displayed no halogen bonding interactions.